A new genus and species of Paranthrenini from Angola (Lepidoptera: Sesiidae) - Bartsch, Daniel; Sáfián, Szabolcs (Zootaxa, 2024)
A new genus and species, Afranthrene cinerea gen. & sp. nov., from Angola is described and depicted. The new genus belongs to the Adixoa Hampson, [1893] genera group and is related to the African genera Fortikona Bartsch & Sáfián, 2023, Rubukona Fischer, 2007 and Thyranthrene Hampson, 1919. The female, early instars and host plant of the new species are unknown.